Development of a Providencia stuartii multilocus sequence typing scheme - Arcari, Gabriele; De Francesco, Alice; Polani, Riccardo; Carattoli, Alessandra; Capitani, Valerio (Frontiers in Microbiology, 2024)
IntroductionThe Providencia genus is assuming greater clinical relevance among infections caused by Enterobacterales also because of its intrinsic and acquired resistance to last-resort antibiotics. However, despite having been known and studied for over 50 years, genomics and taxonomy of the Providencia genus are currently undergoing a deep rearrangement. In this study we aim to outline and characterized the P. stuartii species.MethodsWe retrieved from the GenBank database all genomes labelled as Providencia and performed a comprehensive genome-based species definition founded on average nucleotide identity (ANI) and on alignment-free approaches.ResultsAfter defining the genomes assuredly identifiable as P. stuartii, we devised a MultiLocus Sequence Typing (MLST) and a core-genome MLST (cgMLST) schemes, based on 7 and 2,296 loci respectively.DiscussionThis work hence provides a framework for understanding the role of P. stuartii and of other members of this genus, which should be considered as emerging multidrug-resistant pathogens.